Critical Review of Indonesian Government Legal Policies on The Conversion of Protected Forests and Communal Lands of The Indigenous Batak People around Lake Toba - Imamulhadi Imamulhadi; Nia Kurniati (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2019)
The Development Plan of Sibisa Lake Toba Tourism Area as The National Strategic Area for Tourism by performing a land conversion on protected forests and communal lands had stirred up a problem dilemma regarding the resistance from indigenous people around Toba Lake. It is crucial to be questioned, whether the conversion policy of protected forests and communal lands by the Indonesian Government to develop Sibisa Danau Toba Tourism Area is in accordance with related laws and regulations? As the answer, it can be concluded that the mentioned policy opposes: Article 18b of the 1945 Constitution; Article 15 of the Law of 2009 Number 32 on Environmental Protection and Management; Presidential Regulation Number 81 of 2014 on The Spatial Planning of Lake Toba Area; The Law of 1999 Number 39 on Human Rights; The Law of 2016 Number 6 on Village Government, and lastly, the United Nation Declaration on Human Rights of Indigenous People (UNDHRIP).Telaah Kritis atas Kebijakan Hukum Pemerintah Indonesia terkait Alih Fungsi Hutan Lindung dan Tanah Ulayat Masyarakat Adat Batak di sekitar Danau Toba AbstrakRencana Pembangunan Kawasan Pariwisata Sibisa Danau Toba sebagai Kawasan Strategis Nasional Kepariwisataan dengan melakukan alih fungsi hutan lindung dan tanah ulayat telah menimbulkan permasalahan yang dilematis karena mendapat perlawanan dari masyarakat adat di sekitar Danau Toba. Terhadap kebijakan tersebut penting untuk dipertanyakan apakah kebijakan alih fungsi hutan dan tanah ulayat oleh Pemerintah Indonesia untuk pembangunan Kawasan Pariwisata Sibisa Danau Toba telah sesuai dengan peraturan perundang-undangan yang terkait? Sebagai jawaban atas permasalahan, penulis menyimpulkan bahwa  kebijakan telah bertentangan dengan: Pasal 18b UUD 1945; Pasal 15 Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup; Peraturan Presiden  Nomor 81 Tahun 2014 tentang Rencana Tata Ruang Kawasan Danau Toba; Undang-Undang Nomor 39 Tahun 1999 tentang Hak Asasi Manusia; Undang-Undang Nomor 6 Tahun 2016 tentang Pemerintahan Desa, dan bertentangan dengan United Nations Declaration on Human Rights of Indigenous Peoples (UNDHRIP)Kata Kunci: Alih Fungsi Lahan, Hak Ulayat, Masyarakat Hukum AdatDOI: https://doi.org/10.22304/pjih.v6n3.a2